P325 Risk factors for lymph node involvement in patients undergoing ileal pouch-anal anastomosis for ulcerative colitis complicated by colorectal cancer in the biological years. (16th January 2018) - Rottoli, M; Ghignone, F; Tanzanu, M; Boschi, L; Rizzello, F; Gionchetti, P; Poggioli, G
Abstract: Background: Patients affected by ulcerative colitis (UC) have an increased risk of developing colorectal cancer (CRC), being extensive and long-standing disease associated with neoplasia. Little is known about the predictors for nodal positivity (N+) at time of surgery, especially since the introduction of biologics. The aim of this study was to compare patients undergoing ileal pouch-anal anastomosis (IPAA) for CRC complicating UC for demographic characteristics and perioperative variables depending on the lymph node involvement at the histology. Methods: Since 2002, patients undergoing an IPAA procedure for UC complicated by CRC were retrospectively included. N+ patients were compared with a control group of patients without nodal involvement (N−) for demographic characteristics, use of biological drugs, clinical features. Statistical tests for comparison of continuous or categorical variables were used as appropriate. Results: Forty-eight patients were included. Surgical data are reported in Table 1. Histological findings are detailed in Table 2 while perioperative risk factors for nodal involvement are reported in Tables 3 and 4. Data of biologic drugs are reported in Table 5. Conclusions: A younger age at diagnosis of UC ( p = 0.039) and at IPAA surgery ( p = 0.010) identifies patients at a higher risk of nodal involvement. Duration, activity, and extension of disease at the time of surgery are not associated with nodal positivity. A history of the use of more than one biological agent increases significantly the chance of nodal metastases. Despite the bias of limited numbers and the retrospective nature, our study suggests that younger patients with a history of biological treatment (especially if more than one agent) should undergo a more intensive endoscopic and clinical follow-up.